BACH2: A marker of DNA damage and ageing (2013)
DNA damage and ageing share expression changes involving alterations in many aspects of metabolism, suppression of growth and upregulation of defence and genome maintenance systems. 'Omics' technologies have permitted large-scale parallel measurements covering global cellular constituents and aided the identification of specific response pathways that change during ageing and after DNA damage. We have set out to identify genes with highly conserved response patterns through meta-analysis of mRNA expression datasets collected during natural ageing and accelerated ageing caused by a Transcription-Coupled Nucleotide Excision Repair (TC-NER) defect in a diverse set of organs and tissues in mice, and from in vitro UV-induced DNA damage in a variety of murine cells. The identified set of genes that show similar expression patterns in response to organ ageing (accelerated and normal), and endogenously and exogenously induced DNA damage, consists of genes involved in anti-oxidant systems and includes the transcription factor Bach2 as one of the most consistent markers. BACH2 was originally identified as a partner of the small Maf proteins and antagonist of the NRF2 anti-oxidant defence pathway and has been implicated in B-cell differentiation and immune system homeostasis. Although BACH2 has never before been associated with UV-induced damage or ageing, it shows a strong downregulation in both conditions. We have characterized the dynamics of Bach2 expression in response to DNA damage and show that it is a highly sensitive responder to transcription-blocking DNA lesions. Gene expression profiling using Affymetrix microarray analysis after siRNA-mediated silencing of Bach2 identified cell cycle and transcription regulation as the most significantly altered processes consistent with a function as transcription factor affecting proliferation. © 2013 Elsevier B.V.